Robinson Crusoe - McFadden, Deanna; Akib, Jamel; Defoe, Daniel, 1661?-1731. (New York, NY : Sterling Pub., 2006)
An abridged version of the tale of Englishman Robinson Crusoe, who, after becoming the sole survivor of a 1659 shipwreck, lives on a desert ed island for more than twenty-eight years.
Keywords: Shipwrecks -- Fiction; Survival -- Fiction; Islands -- Fiction; Adventure and adventurers -- Fiction